A Revealing Unpublished Letter of George Whitefield to John Collett Ryland - Gordon, Grant (Baptist quarterly, 2016)
This previously unpublished letter brings to light the friendship between George Whitefield and John Collett Ryland, the Baptist pastor and educator. Details of this relationship and of Ryland's support of the Evangelical Revival are pursued. Further, a careful examination of this brief letter and other sources uncovers that Benjamin Ingham's son Ignatius attended Ryland's boarding school and that Lady Huntingdon was pleased with her nephew's progress. Included is an analysis of what contributed to making Ryland's school so popular among dissenters. In addition, the letter shows the value that Whitefield placed on hymns and how he drew from the hymns of others.